A study on the effects of modified sprint interval trainingon physical fitness test scores and the quantitative and dose-response relationships among Chinese male university students - Huang, Guoyuan; Chen, Yang; Lee, ByungChan; Qiu, Yipeng; Mao, Aqiang; Liang, Maolong; Liu, Maojie (Frontiers in Physiology, 2025)
IntroductionThis study primarily investigates the impact of a 6-week Sprint Interval Training (SIT) intervention on the physical fitness test results of male university students, as well as the dose-response relationship in adjusting the experimental protocol.MethodsA total of 26 male university students (aged 20 ± 2 years; height 174 ± 7 cm; weight 70 ± 14 kg; mean ± SD) with no systematic training in the past 3 months, no physiological diseases, and healthy physical condition voluntarily participated in the experiment. The SIT protocol was designed based on a classic Wingate sprint protocol (4-6 x 30 s sprints with 4 m of recovery), and adjustments were made based on the participants' actual adaptation. The final intervention consisted of 6 weeks of training, three times per week, with 2-3 repetitions of 30-s Wingate sprints (Cd = 0.075, resistance on the ergometer = weight/kg x Cd) and 4–5 m of recovery.ResultsThe results showed significant improvements in key anaerobic capacity indicators after the 6-week intervention: Average Power (AP) increased from 77.4 ± 10.1 to 132.6 ± 21.1 (p < 0.01, Adjusted p < 0.03 ment, with a maximum effect size of 3.344), Peak Power (PP) increased from 102.9 ± 14.5 to 189.5 ± 28.8 (p < 0.01, Adjusted p < 0.02, maximum effect 3.790), and Time to Peak Power (TTP) decreased from 12.3 ± 3.3 to 9.5 ± 2.6 (p < 0.01), confirming that the intervention enhanced the participants' anaerobic capacity. Additionally, The results of the physical fitness test showed significant improvements: standing long jump (SLJ) increased from 2.31 ± 0.15 m to 2.45 ± 0.18 m (significance level p < 0.01), 50 m sprint time decreased from 7.32 ± 0.42 s to 6.98 ± 0.38 s (significance level p < 0.01), and 1,000 m from 235.6 ± 18.4 s to 220.3 ± 16.8 s (significance level p < 0.01). Other metrics such as Body mass, BMI, Vital capacity, and Pull-ups also showed minor increases. Interestingly, Sit forward in a sitting position scores showed a noticeable improvement (from 12.9 ± 6.8 to 15.8 ± 6.2, p = 0.091).DiscussionFurthermore, The adjustment of the training programme has achieved good results, as evidenced by the fact that participants have achieved a training completion rate of over 95%, maintained a moderate subjective fatigue rating (RPE score of 13-15), and no one has withdrawn from the training due to discomfort.ConclusionThe modified SIT protocol proves to be an efficient and practical training method for improving college students' physical fitness.